Santo Tomás y la ontología hilemórfica (2009)
This article presents the relevancy of Aristotle’s hylemorphic ontology.Aristotle himself highlighted the importance and astonishing complexity of the problem of prime matter’s ontological status and he presenting the solution in his doctrine of hylemorphism. As Saint Thomas Aquinasnoted, it is a crucial issue for philosophy because all four, hilemorfism, logic, physics and metaphysics, stand or fall depending on a correct understanding of the ontology of prime matter and of the kind of causal relationship which exist between prime matter and substantial form ingenerable and corruptible substance.